Evaluation of temperature of a full ceramic total knee arthroplasty during MRI examinations. Issue 39 (30th September 2022) - Trieb, Klemens; Artmann, Andreas; Krupa, Michael; Senck, Sasch; Landauer, Franz
Abstract : Background: A diagnosis by magnetic resonance imaging (MRI) is often necessary before surgery of degenerative spine diseases. This can lead to a possible conflict with an inserted implant of the hip or knee. Heat generation or movement could be caused by the magnetic field. The aim of this study is to investigate temperature development in vitro in a 1.5T MRI of a ceramic knee arthroplasty. Methods: A full ceramic, complete metal-free non-constrained primary total knee arthroplasty is investigated. Temperature change was measured between platinum resistors before and after each MRI sequence by change of resistance. The knee implant was placed in a plastic container after the sensors were attached. Then the container was completely filled with ultrasound gel. To document any possible movement of the implant, a grid was placed under the container to document the position of the implant before and after the scans. Results: A total of four standard knee sequences were performed. The temperature at sites 1 to 5 per implant was always documented in the as-is state before MRI and then after each sequence. A total of 5 temperature measurement points were taken per implant. It was found that there were extremely small temperature variations. These were always in the range of less than 1°C. There was no case of movement of the implant triggered by the MRI scan. Conclusions: The experimental investigations carried out here showed homogeneous results with this experimental setup. It is concluded that, at least in vitro, that this ceramic knee implant can be used in MRI examinations without heating or movement.